The Use of ICT and Communication Effectiveness among Secondary School Administrators - Etudor-Eyo, Eno; Emah, Ime Effiong; Ante, Helen Anthony (EDUCARE, 2012)
ABSTRACT: Humanity is currently in an electronic age which is characterized by bridging the gap between distance and time, giving way to information revolution built around information and communication. Therefore, this study obtained data from 396 secondary school administrators through the Administratorsâ Use of ICT Questionnaire (AUIQ) and Administratorsâ Communication Questionnaire (ACQ) to investigate how the use of ICT (Information and Communication Technology) predicts communication effectiveness among secondary school administrators in Akwa Ibom State, Nigeria. The findings were that the extent of administratorsâ use of ICT and the extent of administratorsâ effectiveness in communication are high; there is a significant positive relationship between administratorsâ use of ICT and administratorsâ effectiveness in communication; the effectiveness of secondary school administrators in communication is significantly predicted by the use of ICT. Based on the findings, conclusions were drawn and recommendations made that Government should make ICT tools available in all secondary schools for the administrators; workshops on the use of ICT should be organized from time to time by the Governments and NGOs (Non-Governmental Organizations) for school administrators who are not yet ICT literate; and skilled man-power should be employed to teach those administrators who are still illiterate in this regard by NGOs, the government, and individuals.KEY WORDS: Use of ICT, communication effectiveness, secondary school administrators; and skilled man-power in Nigeria.About the Authors: Dr. Eno Etudor-Eyo and Dr. Ime Effiong Emah are Senior Lecturer at the Faculty of Education UOU (University of Uyo), Nigeria; and Mrs. Helen Anthony Ante is a Researcher at the Ministry of Education, Akwa Ibom State, Uyo, Nigeria. They can be reached at: enoetudor@gmail.com, i.emah001@yahoo.com, and adiahamkara@yahoo.comHow to cite this article? Etudor-Eyo, Eno, Ime Effiong Emah & Helen Anthony Ante. (2012). âThe Use of ICT and Communication Effectiveness among Secondary School Administratorsâ in EDUCARE: International Journal for Educational Studies, Vol.4(2) February, pp.125-136. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 7, 2011); Revised (January 10, 2012); and Published (February 17, 2012).